Distribution of Radopholus similisand Pratylenchus CoffeaeNematodes in Coffee Plantation - Retno Hulupi; Mulyadi .; Bekti Andayani (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
A research to evaluate the difference of damage levels caused by two species nematodes, Radopholus similis and Pratylenchus coffeae on Arabica and Robusta coffee which were planted in the same endemic area have been conducted at Kalibendo (700 m asl. climate type B) and Blawan coffee estate (1200 m asl., climate type D) for two years. The results showed that in the medium highland (700 m asl.) R. similis attacked Arabica coffee with necrotic root scale higher than surface Robusta coffee. Distribution of R. similis population in the 50 cm depth below soil surface was likely with their root distribution. On the other hand P. coffeae in 30 cm depth below soil therefore their resistance to R. similis was more likely due to the escape reason, as result of their different distribution population of those species in different depth. Key words : Radopholus similis, Pratylenchus coffeae, Arabica coffee, Robusta coffee, distribution population.